1987
DOI: 10.1017/s0195941700067254
|View full text |Cite
|
Sign up to set email alerts
|

Tuberculosis in Hospital Personnel

Abstract: Tuberculosis (TB) skin testing practices and the prevalence and inherent risk of TB infection among hospital employees in 167 North Carolina (NC) hospitals were determined from a 79% (132/167) response to a tuberculosis screening questionnaire. Preemployment TB skin testing was performed by 98% of responding hospitals, primarily (87%) by the Mantoux method. TB skin test reactions of ≥ 10 mm were interpreted as significant by 72% and at the appropriate time interval of 48 to 72 hours after administration by 80%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

1992
1992
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 13 publications
0
11
0
Order By: Relevance
“…34 This higher conversion rate was attributed to immunologic boosting, because conversions on tuberculin testing were associated with older age but not with exposure. 34 In four studies in which the ratio of the number of workers to the annual number of admissions for tuberculosis was between 18 and 92, the annual risk of infection ranged from 1.7 to 3.9 percent 28,32,36,43 and was correlated with actual exposure in two of the institutions. 32,43 In hospitals where there were more than 200 admissions annually for tuberculosis or where the ratio of workers to annual admissions was less than 10, infection occurred in 1 to 10 percent of workers each year.…”
Section: E Stimates Of the R Isk Of T Uberculous D Iseasementioning
confidence: 99%
See 3 more Smart Citations
“…34 This higher conversion rate was attributed to immunologic boosting, because conversions on tuberculin testing were associated with older age but not with exposure. 34 In four studies in which the ratio of the number of workers to the annual number of admissions for tuberculosis was between 18 and 92, the annual risk of infection ranged from 1.7 to 3.9 percent 28,32,36,43 and was correlated with actual exposure in two of the institutions. 32,43 In hospitals where there were more than 200 admissions annually for tuberculosis or where the ratio of workers to annual admissions was less than 10, infection occurred in 1 to 10 percent of workers each year.…”
Section: E Stimates Of the R Isk Of T Uberculous D Iseasementioning
confidence: 99%
“…17 Studies using data from disease registries (summarized in Table 1) have reported an estimated risk ratio of 0.6 to 2.0, indicating at most only a modest increase in risk. 20,21,23,[26][27][28] Both cohort and disease-registry studies may be limited by the inability to distinguish occupational from nonoccupational exposure. These studies may underestimate the risk because of the failure to standardize for age 20,[26][27][28] or because the working population is younger and has a lower incidence of tuberculosis than the general population (the "healthy-worker effect").…”
Section: E Stimates Of the R Isk Of T Uberculous D Iseasementioning
confidence: 99%
See 2 more Smart Citations
“…Workers with potential occupational exposure in the mid-1990s were considered to be those in hospitals, nursing homes, homeless shelters, and correctional facilities (estimated total 5.3 million). For hospitals OSHA estimated lifetime risk of TB infection due to occupational exposure for workers in hospitals with good exposure controls [Aitken et al, 1987], some controls [Price and Rutala, 1987], and poor controls [Boudreau et al, 1997]. In each case a range of excess risks was given which corresponded to the range of background rates in different parts of the country, since excess risk depends on the level of background risk.…”
Section: Tuberculosismentioning
confidence: 99%